Optimización estratégica: un plan integral para supermercados Wong - Bernard Garcia, Isabella María (2023)
This work has been carried out to obtain the University degree in administration. To do this, Cencosud S.A. was chosen as the research company, to be more specific, the supermarket business unit in Peru: Wong. The development of this work consists of seven chapters where strategies will be deepened, explained, and proposed to enable the company to maintain its leadership in the national territory. In the first stage, the variables of the macro-environment and micro-environment were reviewed. This analysis allowed for the identification of the opportunities and threats in the sector where the company operates and the strengths and weaknesses of Wong chain. With this information, graphical tools learned during the 5 years of the program were used to explain the current situation of the company and its environment. In the final stage, the formulation and implementation of the strategy were carried out, creating a strategic plan applied to the year 2024 for the chain. This plan modified the current mission, vision, and organizational structure, and assessed the financial impact it would have on the income statement. Finally, new indicators were considered for proper strategic control according to the proposal.